"Don't call it work": an interpretative phenomenological analysis of volunteer firefighting in young adults based on the volunteer process model. (17th March 2023) - Nowakowska, Iwona
Abstract : The number of people engaging in volunteer firefighting is on the decline. It is therefore important to understand what factors on a personal and social level and from the three stages of the volunteer process model – antecedents, experiences and consequences – might be linked to starting and sustaining engagement in volunteer firefighting. To do this, a qualitative, interview-based study was carried out using a sample of ten volunteer firefighters from across Poland. The data were gathered and analysed using the interpretative phenomenological analysis methodological framework. The data enabled information regarding the stage of the volunteer process and the motivations behind the engagement to be grouped and interpreted. The implications for retention strategies are set out, with a particular focus on the social support of firefighters, the role of coping skills, relationships with the local community, the quality of relationships within the firefighting brigade, the personal development of volunteers and how firefighters make meaning of their service.